2007
DOI: 10.2174/187231207783221402
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Leflunomide by Mouse and Human Liver Microsomes

Abstract: Leflunomide was found to be metabolized predominantly to A77-1726 and two novel hydroxylated metabolites, M1 and M2, in microsomes while A77-1726 was only biotransformed to M1. M1 and M2 were proposed to be the hydroxylated alpha-cyanoenol form of A77-1726 and the hydroxylated 5 methyl-isoxazole form of leflunomide, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The UPLC and QTRAPMS systems were controlled by Analyst 1.4.2 software (Applied Biosystems). All the metabolic profiling experiments related to LEF and its metabolites have been previously discussed 15. Product ion scanning (PIS) experiments were performed to profile both LEF and its metabolites, APAP and NAPQI‐GSH in the microsomal incubation samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UPLC and QTRAPMS systems were controlled by Analyst 1.4.2 software (Applied Biosystems). All the metabolic profiling experiments related to LEF and its metabolites have been previously discussed 15. Product ion scanning (PIS) experiments were performed to profile both LEF and its metabolites, APAP and NAPQI‐GSH in the microsomal incubation samples.…”
Section: Methodsmentioning
confidence: 99%
“…Orally administered LEF is almost completely converted into its pharmacological active metabolite, A77‐1726, and the circulating concentrations of LEF are mostly below the limit of detection 14. Both LEF and A77‐1726 were found to be metabolized in vitro using CD‐1 mouse and human liver microsomes to two hydroxylated metabolites, M1 and M2 15. Each pair of these compounds (LEF/A77‐1726 and M1/M2) is isobaric and structurally similar (Fig.…”
mentioning
confidence: 99%
“…The latter is supported by studies of leflunomide in cultured hepatocytes, which indicated that Cytochrome P450 mediated metabolism is a prerequisite for leflunomide induced liver injury, whereas teriflunomide is directly, albeit less significantly toxic [12]. Metabolites of teriflunomide have not been observed in human plasma, but studies with human liver microsomes have shown that teriflunomide can be converted via hydroxylation to a metabolite (M1), whereas leflunomide can be converted to either teriflunomide or a different metabolite (M2, also by hydroxylation) [13,14]. If the enzymes responsible for formation of M2 are different from the well characterized conversion pathway of leflunomide to teriflunomide, reduced activity of CYP2C19 is likely to result in increased formation of M2, which may be the toxic metabolite contributing to the side effects associated with leflunomide.…”
Section: Discussionmentioning
confidence: 99%
“…Leflunomide is metabolized by polymorphic phase I enzymes, particularly CYP1A2 (cytochrome P450 1A2), CYP2C and CYP3A4 (cytochrome P450 3A4), but studies [66][67][68][69][70][71] addressing the role of altered metabolism genetically determined and the risk of developing hypersensitivity reactions to leflunomide are still insufficient.…”
Section: Recent Advances In Genetic and Metabolic Biomarkers Of Hypermentioning
confidence: 99%